Asymmetric Pass-through Effects of Oil Price Shocks and Exchange Rates on Inflation in Nigeria: Evidence from a Nonlinear ARDL Model - Sa’ad, Suleiman; Usman, Ali Baba; Omaye, Solomon Ochada; Yau, Hamisu (European Scientific Journal, ESJ, 2023)
This paper employs the linear autoregressive distributed lag (ARDL) model, the asymmetric nonlinear ARDL (NARDL) model developed by Shin, et al (2014) to examine the asymmetric effect of oil price and exchange rates pass-through on inflation in Nigeria over a period of 1970 to 2020. The result of the asymmetric test revealed the existence of asymmetries among the variables of the study, suggesting that there is a nonlinear interaction among the variables used in the study. This validates the choice of a non-linear ARDL model for the study. Results of the long-run estimates show that rising (Positive) oil price shocks have a greater impact on inflation than falling (negative) oil price shocks. Furthermore, it is evident from the result that the depreciation of the exchange rate has a much and significant effect on inflation than the appreciation of the exchange rate in Nigeria. However, a rising interest rate increases inflation by 0.84 per cent while a falling interest rate increases inflation by 0.85 per cent. This implies that the effect of negative interest rate on inflation is higher than its positive effect on inflation, though, by a smaller amount of about 0.01 per cent. Again, the short-run dynamic model revealed a high speed of convergence of more than 90% from the short-run disequilibrium. During the study period, the oil price fluctuations showed a significant and incomplete pass-through to both exchange rates and inflation in Nigeria. Moreover, the results suggest that positive oil price changes have a larger impact than the negative ones, that the effect of an oil price shock on inflation and exchange rates is larger in the long-run than in the short-run, and that there is incomplete pass-through effect of oil price on domestic inflation and exchange rates. Based on the findings, the study recommends policies that set oil prices and exchange rates within reasonable limits to check inflation in Nigeria and should diversify its economy as well as withdraw the current subsidy regime completely.